Malaysian consumer acceptance and preference towards three types of local honey based on sensory characteristics - Saludin, Siti Farhana (2019)
Honey is proven to have a lot of benefits if it is consumed continuously. Usually, honey consumed as foods as well as for medicinal values, cosmetics, etc. Local honey is the most well-known honey in the market and the uniqueness of its characteristics and quality has made it receive a high demand from consumers. As Malaysia can only fulfil 4% of local honey demanded, thus Malaysia needs to import honey from other producer countries to fully fulfil the demand. The most crucial issue that occurred in the honey market is the dominated of artificial honey that has been manipulating the quality and thus confusing the consumers to purchase good quality of pure local honey. This study was carried out mainly to determine Malaysian consumer acceptance and preference towards three types of local honey (Tualang honey, Stingless bee honey (locally known as Kelulut honey), and Mellifera honey) based on sensory characteristics. Four specific objectives of the study were established; 1) to determine sensory characteristics of three types of local honey, 2) to investigate the association between consumers’ preferences towards three types of local honey based on sensory characteristics and socio-demographic profiles, 3) to determine consumers’ acceptance towards three types of local honey based on sensory characteristics, and 4) to investigate the most influential factors that influenced consumers’ preferences towards three types of local honey. Purposive sampling was used to select 406 respondents being honey consumers representing Klang Valley, Malaysia. Face-to-face interviews were carried out with the respondents using a structured questionnaire, consisting of closed and open-ended questions. The data was analysed using several statistical analyses such as descriptive analysis, Chi-square analysis, one-way analysis of variance (ANOVA) analysis, factor analysis, and logistic regression analysis. Further, sensory evaluation was used to analyze the sensory characteristics of three types of local honey among the respondents. Based on the descriptive analysis, majority of the respondents consumed honey for less than 50 times per year with less than 500ml per year. Medicinal value of the honey was the important reason for the respondents to consume honey. The results of mean ranking analysis showed that most of the respondents preferred honey with sweet in taste and more viscous. Chi-square analysis was carried out and the results revealed that race and marital status were significant with consumers’ preferences towards three types of local honey based on sensory characteristics. The results of one-way analysis of variance (ANOVA) analysis indicated that most of the respondents preferred the moderately light color of Tualang honey and Mellifera honey, and slightly lighter colour of Stingless bee honey. Overall, the respondents were more preferred Mellifera honey compared to other types of honey. Meanwhile, factor analysis revealed that there were nine (9) factors such as granular, colour, bitterness, sweetness, viscosity, spices aroma, sourness, herbal aroma, and fruity aroma influenced the respondents’ preferences towards three types of local honey based on sensory characteristics. Finally, the results from logistic regression analysis revealed that viscosity was the most influential factor that influenced consumers’ preferences towards three types of local honey when deciding to purchase. In conclusion, the results from the analyses showed that Mellifera honey was the most preferred honey among the respondents and viscosity attribute was the major attribute that influenced consumers’ preferences towards three types of local honey. The findings are beneficial for all local honey producers especially Mellifera honey producers as this study has significantly proved that Mellifera honey was the most preferable honey among the consumers. Thus, the government needs to promote and support the honey industry as there are some unique characteristics of local honey which have significantly attracted consumers for consuming the honey. The government and other agencies also need to establish the local honey standard and publish it for public use. Besides, the government also should organize various programs in order to spread the information on the quality standard of local honey, so that the producers and consumers could improve their knowledge and confident about the local honey.